ACE Inhibitor-Induced Angioedema of the Bowel - Tabitha Campbell; Bradley Peckler; Raleigh David Hackstadt; Austin Payor (Case Reports in Medicine)
Angiotensin converting enzyme inhibitor ACEI-induced angioedema of the intestine is a rare occurrence and often unrecognized complication of ACEI. We present a case of a 45-year-old Hispanic female with angioedema of the small bowel progressing to facial and oral pharyngeal angioedema. Patients are typically middle-aged females on ACEI therapy who present to the emergency department with abdominal pain, nausea, vomiting, and diarrhea. This is a diagnosis of exclusion, and physicians must have a high index of suspicion to make the diagnosis. Symptoms typically resolve within 24–48 hours after ACE inhibitor withdrawal. Recognizing these signs and symptoms, and discontinuing the medication, can save a patient from unnecessary, costly, and invasive procedures.